Scaling Colonial Violence: One Day Celebrations in Fremantle, WA - Zuzanna Kruk-Buchowska (Anglica. An International Journal of English Studies)
The aim of this paper is to analyse the Fremantle City Council’s decision to celebrate One Day on January 28th 2017 instead of the usual Australia Day on January 26th, as well as the ensuing media debate between its supporters and opponents, especially Noongar leaders and WA Government. The discourse is examined in the context of the disruption of colonial violence. The City of Fremantle, as a place, itself serves as a point of reference for the analysis. Although today Fremantle is often perceived as a “progressive island” in a largely conservative Western Australia, the Fremantle prison and nearby Rottnest Island are stark reminders of the maltreatment of the Whadjuk people after the formation of the Swan River Colony in 1829.